Effect of platelet-rich fibrin gel combined with alginate dressing on healing of active venous leg ulcers: a randomized clinical trial - Feifei Cui; Rongting Wang; Zhen Xu; Qianqian Chen (Frontiers in Medicine, 2026)
Importance Active venous leg ulcers (VLUs) represent a challenging chronic wound condition with prolonged healing trajectories, high recurrence rates, and substantial physical and psychological burden. Despite standard compression therapy, a significant proportion of VLUs fail to achieve timely closure, underscoring the need for effective conservative treatment options. Objective To evaluate the efficacy and safety of autologous platelet-rich fibrin (PRF) gel combined with alginate dressing in promoting complete healing of active VLUs. Design, setting, and participants A single-center, prospective, randomized controlled trial conducted between January 2023 and October 2025 at the vascular surgery and wound specialty outpatient clinics of a tertiary hospital in China. The 86 participants were patients with active VLUs (CEAP C6) who received standardized wound bed preparation and compression therapy. Participants were recruited through consecutive admissions. Interventions Patients were randomly assigned 1:1 to receive either PRF gel combined with alginate dressing applied weekly (treatment group, n = 43) or ozonated oil combined with alginate dressing applied three times weekly (control group, n = 43) for 12 weeks. Main outcomes and measures Primary efficacy endpoint was complete wound healing rate at 12 weeks. Secondary outcomes included healing efficacy (categorized as complete, markedly effective, effective, or ineffective), changes in pain intensity (Visual Analog Scale), and changes in anxiety levels (State–Trait Anxiety Inventory). Results The PRF-alginate group achieved a significantly higher complete healing rate at 12 weeks compared with the control group (83.7% vs. 30.2%; risk difference, 53.5% [95% CI, 35.9–71.1%]; relative risk, 2.8 [95% CI, 1.7–4.4]). The median time to healing was 7.6 weeks (95% CI, 6.0–8.7) in the PRF group and was not reached in the control group (log-rank p = 0.006). PRF-alginate treatment was the strongest independent predictor of complete healing (odds ratio, 25.53 [95% CI, 4.95–131.50]), while baseline wound area was negatively associated with healing (odds ratio, 0.76 [95% CI, 0.64–0.90]). The PRF-alginate group showed a greater improvements in state anxiety scores (mean difference, 1.4 [95% CI, 0.0–2.8]) and trait anxiety scores (mean difference, 1.4 [95% CI, 0.1–2.7]) compared with the control group. No significant between-group difference was observed in pain scores (mean difference, 0.3 [95% CI, −0.1 to 0.7]). No serious adverse events were reported. Conclusions and relevance The combination of platelet-rich fibrin gel and alginate dressing accelerates wound healing, shortens healing time, reduces pain and anxiety, and has a favorable safety profile in patients with active venous leg ulcers. This biologically grounded, technically simple, and cost-effective approach is a promising conservative treatment option for outpatient and primary care settings, particularly for elderly and geographically underserved populations who may not benefit adequately from conventional therapies requiring frequent clinic visits. Clinical trial registration Clinicaltrials.gov Identifier: ChiCTR2400087844